БЎЛАЖАК ЖИСМОНИЙ МАДАНИЯТ ЎҚИТУВЧИСИГА ЙЎНАЛТИРИЛГАН ТАЪЛИМ ПАРАДИГМАСИ - Татлимуратов, А.Т. (SCIENCE and SOCIETY, 2024)
The article discusses pedagogical innovations in the system of physical culture in the upbringing of the younger generation, the peculiarities of the state of introduction of new technologies and forms, as well as the pedagogical possibilities of the educational paradigm focused on the teacher of modern physical culture.
Keywords: paradigma; physical culture; abilities; technology; program; innovation; creative activity